2011
DOI: 10.1098/rstb.2010.0357
|View full text |Cite
|
Sign up to set email alerts
|

Forward from the crossroads of ecology and evolution

Abstract: Community genetics is a synthesis of community ecology and evolutionary biology. It examines how genetic variation within a species affects interactions among species to change ecological community structure and diversity. The use of community genetics approaches has greatly expanded in recent years and the evidence for ecological effects of genetic diversity is growing. The goal of current community genetics research is to determine the circumstances in which, and the mechanisms by which community genetic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 60 publications
0
40
0
1
Order By: Relevance
“…Although inter-and intraspecific diversity are important for communities (multi-species) and populations (single-species), respectively, several studies have also shown that inter-and intraspecific diversity do not operate independently in communities. In fact, intraspecific diversity interacts with interspecific diversity and can profoundly affect community performance (Agrawal, 2003;Vellend and Geber, 2005;Whitham et al, 2006;Hersch-Green et al, 2011;Rowntree et al, 2011). For example, increased intraspecific diversity of Ammophila breviligulata, a dominant plant in some sand dune ecosystems, changed the relationship between interspecific diversity and the above ground biomass of the whole community (Crawford and Rudgers, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although inter-and intraspecific diversity are important for communities (multi-species) and populations (single-species), respectively, several studies have also shown that inter-and intraspecific diversity do not operate independently in communities. In fact, intraspecific diversity interacts with interspecific diversity and can profoundly affect community performance (Agrawal, 2003;Vellend and Geber, 2005;Whitham et al, 2006;Hersch-Green et al, 2011;Rowntree et al, 2011). For example, increased intraspecific diversity of Ammophila breviligulata, a dominant plant in some sand dune ecosystems, changed the relationship between interspecific diversity and the above ground biomass of the whole community (Crawford and Rudgers, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, this effort focused on individual species and populations, but more recent studies in 'community genetics' and related disciplines recognize that it might be necessary to unite the diverse theories, concepts and techniques employed in community ecology, evolutionary biology, genetics and genomics to understand the ecology and evolution of interactions among species within communities [3][4][5][6][7]. Community genetics has lured many biologists with diverse interests with the hope that a successful unification of these seemingly disparate fields will bring novel insight and greater predictive power to address basic and applied problems in biology.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive responses of plants to climate change are intimately coupled with soil communities and soil function because genetic differences among individual genotypes within a plant species may have "extended" consequences for communities and ecosystems, including those belowground (reviews by Whitham et al 2006Whitham et al , 2012Hughes et al 2008;Rowntree et al 2011;Schweitzer et al 2012). Though evolutionary impacts on ecosystems are not always established (as reviewed in Fussmann et al 2007;Matthews et al 2011;Schoener 2011), plants frequently act as foundation species whose genetic structure and function are important to understand because they create stable conditions that support unique communities of interacting species (Dayton 1972).…”
Section: Introductionmentioning
confidence: 99%